Effect of whole exome sequencing in diagnosis of inborn errors of metabolism and neurogenetic disorders: A review articles - Shakiba, Marjan; keramatipour, Mohammad (Iranian Journal of Child Neurology, 2018)
Background: Inborn errors of metabolism are complex disorders with huge variety in clinical manifestations. Metabolic disorders have overlapping clinical pictures with other genetic disorders especially neurogenetic diseases. It causes hardship in diagnosis of metabolic and neurogenetic diseases in some occasions. There is growing rise for using whole exome sequencing in diagnosis of genetic disease during recent years result from decreasing its cost. Methods: We reviewed articles by search in medline database to evaluate impact of whole exome sequencing in diagnosis of metabolic and neurogenetic diseases in clinic field. Results: Review declared whole exome sequencing is effective in recognizing metabolic and neurologic diseases especially in complex cases. Diagnostic yield of whole exome sequencing in identifying metabolic and neurogenetic disease has large variety, ranging from 16% to 68% that increase during recent years. It has ability to change patients’ management in 2-44% of cases depend on different studies. Whole exome sequencing can provide new information about new disease, new variants and phenotypes. Careful interpretation of data obtained by WES and evaluation of correlation between clinical manifestation and results is necessary for clinical application of this technology. Conclusions: Whole exome sequencing is useful way for diagnosis of metabolic and neurogenetic diseases essentially in puzzling cases.